PENINGKATAN MINAT BERWIRAUSAHA MAHASISWA UNIVERSITAS ISLAM INTERNASIONAL DARULLUGHAH WADDA'WAH - Alkaff, Muhammad (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2023)
The problem of the growth of young enterpreneurs in Indonesia is still a polemic that has not been clearly defined. Therefore, it is necessary to prepare potential next generation in the field pf entrepreneurship. In this preparatory agenda, entrepreneurship education in tertiary institutions will play a crucial role, apart from the influence of classmates in fostering student interest in entrepreneurship. This research method uses a quantitative approach with a casual perspective. The population in this study were all student of Darullughah Wadda’wah International Islamic University class of 2020/2021, totaling 951 students from 8 study programs. While the sampling technique in this study used the simple random sampling method, the number of wich was calculated using the slovin formula so that the number of samples was 100 respondents. The analysis technique used is structural equation modeling with AMOS program tools. The research results obtained in this study are (1) entrepreneurship education has a significant effect on the interest in entrepreneurship; (2) entrepreneurship education has a significant effect on social media influence of classmate; (3) social influence of classmate influences interest in entrepreneurship.